A Molecular Phylogeny Of Bornean Tree Frog (Amphibia : Anura : Rhacophoridae) From Genus Polypedates - Sarina, Mat Yasin (Universiti Malaysia Sarawak (UNIMAS), 2011)
The evolutionary biology of genus Polypedates was not well understood. Thus, molecular phylogeny of the genus Polypedates were studied by using mitochondrial ribosomal of partial 16S gene, in order to elucidate the phylogenetic relationship among members of genus. Tissues samples were collected from six different localities, namely UNIMAS East Campus, Bario, Similajau National Park, Bako National Park, Matang Wildlife Centre and Kubah National Park. A total of 489 bp of mitochondrial ribosomal of partial 16S gene from 25 samples were analysed using molecular technique approach (DNA extraction, PCR amplification, and direct sequencing). From this study, there are two major monophyletic groups were appeared and sister to each other supported by highly bootstrap values of 100% in Neighbour-Joining (NJ), Maximum Parsimony (MP), Maximum Likelihood (ML) and Bayesian Analysis. Hence, Polypedates otilophus was identified as basal by outgroup rooting which fully supported by highly bootstrap values of NJ, MP, ML and Bayesian Analysis. Moreover, Polypedates leucomystax, Polypedates macrotis, Polypedates colletti and Polypedates otilophus were was sister groups. Mitochondrial ribosomal 16S gene is a useful genetic marker for species divergence for all tree frogs and this study should be extends to elucidate the phylogenetic analysis all species in the genus including new species of Polypedates chlorophthalmus.